Temporomandibular joint disorders – a lookback in time - Baig, Nazish; Parasrampuria, Nikita; Yeshwante, Babita; Mazumder, Debojyoti (International Journal of Dental Research, 2017)
The variety of terms used has contributed to a great amount of confusion that exists in this already complicated field of study. Lack of communication and coordination of research efforts often begins with differences in terminology. Therefore in an attempt to coordinate efforts, the American Dental Association began to use TMD to include all functional disturbances of the masticatory system. The article reviews the research work done by various authors pertaining to the disorders of the temporomandibular joint.